2017
DOI: 10.1590/s0102-865020170205
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic membrane as an option for treatment of acute Achilles tendon injury in rats

Abstract: 1 5-Experimental SurgeryActa Cir Bras. 2017;32(2):125-139 Abstract Purpose: To evaluate the effect of human amniotic membrane (hAM) fragment on inflammatory response, proliferation of fibroblast and organization of collagen fibers in injured tendon. Methods: Sixty rats were divided into 3 groups: C -surgical procedures without tendon lesion and with simulation of hAM application; I -surgical procedures, tendon injury and simulation of hAM application; T -surgical procedures, tendon injury and hAM application. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 31 publications
5
24
0
Order By: Relevance
“…The histological analysis demonstrated that the inflammatory response in group T was less intense at all stages of the process than that in group C, favoring a more organized progression. The considerable decrease in the number of inflammatory cells at 14 days and 21 days in group T demonstrated that the HAM did not increase the inflammatory response in the wounds, which corroborates their low immunogenicity and its possible allogeneic use [18][19] .…”
mentioning
confidence: 54%
See 2 more Smart Citations
“…The histological analysis demonstrated that the inflammatory response in group T was less intense at all stages of the process than that in group C, favoring a more organized progression. The considerable decrease in the number of inflammatory cells at 14 days and 21 days in group T demonstrated that the HAM did not increase the inflammatory response in the wounds, which corroborates their low immunogenicity and its possible allogeneic use [18][19] .…”
mentioning
confidence: 54%
“…In addition, the harvesting of the amniotic membrane does not offer any risk to the newborn or the parturient, and the membrane can be easily obtained and stored in laboratories for later use. The use of these biomaterials does not raise ethical or religious conflicts, besides being a cost-effective alternative, when compared to the isolation and culture of stem cells, which require more complex processes [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] . Therefore, the results confirm the biocompatibility of the HAM and that its application promoted a greater formation of collagen fibers and total re-epithelialization of the wound area.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(percutaneous or open) and the route of access (lateral or posterior incision) [2] [13] [18] [19] [20]. Ehrlich et al [21] and Arruda et al [22] described a technique for complete tenotomy that is easily reproduced in rats, but without description of the plantaris tendon or exact localization of the tendon section.…”
Section: Discussionmentioning
confidence: 99%
“…Despite improved knowledge of Achilles tendon pathology, the optimal treatment and the best rehabilitation protocol after an acute rupture remain a matter of controversy in orthopaedic and sports medicine [35]. In experimental studies on animal tendons, partial or complete surgical tenotomy is the most commonly used method for inducing injury [36] and these models appear useful for investigating the effect of therapies in acute tendon injuries [20]. …”
Section: Discussionmentioning
confidence: 99%